Invasive Argentine ants prey on Bulwer’s petrels nestlings on the desertas islands (Madeira) but do not depress seabird breeding success - Boieiro, Mário (2018)
Invasive ants have the potential to cause severe impacts on the structure and composition of native invertebrate communities and interfere with the natural processes of pollination and seed dispersal. Less frequently reported, direct and indirect impacts on vertebrates, namely birds, are also known to occur. The Argentine ant Linepithema humile is one of the worst invasive species worldwide, and is responsible for economic and ecological impacts in Madeira since its introduction. Previous reports indicated that Argentine ants may be a frequent predator of nestlings on the Desertas Islands which harbour internationally important seabird colonies. Here, we provide a survey of the records of bird predation by Argentine ants in the Desertas. Furthermore, we also assessed if these invasive ants affected the most abundant crevice-nesting seabird on Deserta Grande, the Bulwer’s petrel Bulweria bulwerii, by nest monitoring in the years of 2014–2016. We found that breeding success varied annually between 0.56 and 0.63 chicks produced per nesting attempt. Ant predation of chicks was observed in only two out of 294 study nests. Furthermore, no relationship was found between local abundance of Argentine ants and breeding success of Bulwer’s petrels. We conclude that Argentine ants do not seem to pose a major threat to nesting petrels on the Desertas, although we acknowledge the possibility that environmental changes and episodic population explosions of this invasive species may lead to a greater impact on seabirds’ reproductive success.